Parthenocarpy-related genes induced by naphthalene acetic acid in oil palm interspecific O × G [Elaeis oleifera (Kunth) Cortés × Elaeis guineensis Jacq.] hybrids - Montoya, Carmenza; Mejia-Alvarado, Fernan Santiago; Botero-Rozo, David; Ayala-Diaz, Ivan Mauricio; Romero, Hernan Mauricio (Frontiers in Genetics, 2023)
The transcriptome changes underlying the parthenocarpy fruit formation in oil palm interspecific OxG hybrids (Elaeis oleifera (Kunth) Cortés x Elaeis guineensis Jacq.) induced by exogenous naphthalene acetic acid (NAA) applications were examined comparing three treatments: NAA, Pollen, and a control without any application. The treatments were applied at three phenological stages of the inflorescences: i) PS 603, pre-anthesis III, ii) PS 607, anthesis, and iii) PS 700, fertilized female flower. The expression profile was studied at three separate times: five minutes post-treatment (T0), 24 hours post-treatment (T1), and 48 hours post-treatment (T2). The RNA sequencing (RNA seq) approach was used with 27 OxG interspecific hybrid palms for 81 raw samples (OxG palms/treatment/stage/time) sequenced with the Illumina NovaSeq 6000 platform. Several families of transcriptions factors (TF) were identified as differentially expressed genes between NAA and Pollen treatment. The expression of the most relevant TF families such as WRKY, Ethylene-responsive transcription factor (ERFs), Auxin response factor (ARFs), MYB, bHLH, and Heat stress transcription factor (HS) was variable and dependent on the stage and time post-treatment. The ARF, SAUR, IAA, and GA genes, necessary in the signaling pathways involved in parthenocarpy phenomena, also showed transcriptional profiles like those reported previously for other species. This detailed knowledge about the molecular mechanisms involved in parthenocarpy could be used to facilitate the future development of genome editing techniques that enable the production of parthenocarpic OxG hybrid cultivars without growth regulator application.